مقتضى الجمع بين العقود في الفقه الإسلامي والقانون، دراسة تحليلية: The Implications of Combining Contracts in Islamic Jurisprudence and Law, an Analytical Study - Mohmmed ALwadeai, Jaber Abdullah; Bin Salleh, Ahmad Zaki (AL-HIKMAH: INTERNATIONAL JOURNAL OF ISLAMIC STUDIES AND HUMAN SCIENCES, 2024)
ملخص البحث يتناول هذا البحث دراسة مقتضى الجمع بين العقود، وبخاصة عقد الإجارة المنتهية بالتمليك، من منظور شرعي وقانوني، وذلك نظرًا لتطور المعاملات المالية وانتشار هذه العقود في التعاملات التجارية والمصرفية الحديثة. ويهدف البحث إلى ضبط هذه المعاملات وفق أحكام الشريعة الإسلامية والقانون، بما يحقق العدالة ويمنع الغش والتحايل المؤدي إلى الربا، مع توضيح آراء الفقهاء القدامى والمعاصرين وهيئات الفتوى والرقابة الشرعية حول هذا النوع من العقود. ويمكن إظهار مشكلة البحث في عدم وضوح العقود المالية المركبة وضوحًا كاملاً ينفي عنها اللبس والشك والتحير، مما يدعو إلى بيان مفهوم هذه العقود وطبيعتها القانونية، والواقع العملي لها في المؤسسات المالية المصرفية الإسلامية، كما يركز البحث على تحليل النصوص القانونية ومقارنتها بالأحكام الشرعية، مع دراسة القوانين المطبقة في كل من دولة الإمارات العربية المتحدة وجمهورية مصر العربية، لبيان أوجه التشابه والاختلاف في تنظيم هذه العقود. ويعتمد البحث على المنهجين التحليلي والمقارن للوصول إلى نتائج توضح مفهوم العقود المركبة وطبيعتها وأحكامها، مع إبراز دورها في تلبية احتياجات السوق المعاصرة، سواء في الأنشطة الاستثمارية أو التمويلية، مع الحرص على تجنب الوقوع في المحظورات الشرعية. وخلص البحث إلى أن الجمع بين العقود جائز بشرط عدم التعارض مع نصوص شرعية أو قانونية، وأن عقد الإجارة المنتهية بالتمليك يُعد من العقود المركبة المشروعة إذا استوفى شروط الصحة الشرعية، وقد نظمته القوانين تحت مسمى التأجير التمويلي. كما أكد البحث على أهمية تطوير التشريعات لمواكبة تطور هذه العقود، وتوفير صيغ قانونية واضحة تسهم في توحيد الرؤى الشرعية والقانونية، بما يدعم الاستقرار المالي والاقتصادي، ويعزز ثقة المتعاملين في هذه العقود الحديثة. ABSTRACT This research addresses the study of combining contracts, particularly the lease-to-own contract, from a Shari'ah and legal perspective. This focus arises due to the evolution of financial transactions and the widespread use of such contracts in modern commercial and banking practices. The research aims to regulate these transactions in accordance with Islamic Shari'ah and legal provisions to ensure justice and prevent fraud and deception that may lead to usury (riba). It also seeks to clarify the views of classical and contemporary jurists, as well as fatwa-issuing bodies and Shari'ah supervisory boards, regarding this type of contract. The research problem lies in the lack of full clarity surrounding composite financial contracts, which leads to ambiguity, doubts, and confusion. Therefore, the study highlights the concept and legal nature of these contracts, as well as their practical application in Islamic financial institutions. It emphasizes the analysis of legal texts and their comparison with Shari'ah rulings, along with examining the laws applied in both the United Arab Emirates and the Arab Republic of Egypt to identify similarities and differences in regulating these contracts. The research adopts analytical and comparative methodologies to derive findings that clarify the concept, nature, and rulings of composite contracts. It highlights their role in meeting the needs of the modern market, whether in investment or financing activities, while ensuring compliance with Shari'ah principles. The research concludes that combining contracts is permissible, provided there is no conflict with Shari'ah or legal provisions. Furthermore, the lease-to-own contract is considered a legitimate composite contract if it fulfills the requirements of Shari'ah validity. It has also been regulated under the term "financial leasing" in legislation. The study underscores the importance of developing laws to keep pace with the evolution of such contracts and providing clear legal frameworks that unify Shari'ah and legal perspectives. This approach supports financial and economic stability and enhances stakeholders' confidence in these modern contracts.